IMPACT OF THE COVID-19 PANDEMIC ON STUDENTS STKIP AHLUSSUNNAH BUKITTINGGI - Alexander Syam (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2022)
The purpose of this study was to examine and analyze the impact of the COVID-19 pandemic on the education of Stkip Ahlussunnah Bukittinggi students who experienced many obstacles in its implementation. The method used in the completion of this research uses the Google Scholar, Science Direct and ERIC databases. The results obtained are that there are various impacts caused by the Covid-19 virus, negative impacts that occur in the learning process related to online learning techniques and the psychology of students, parents and educators who need adjustments in learning methods. The positive impact we need to know is that education about information technology has increased drastically. There are new opportunities for academics to develop learning methods through distance learning models. Online learning has several impacts on students, namely online learning still confuses students; students become passive, less creative and productive; accumulation of information/concepts on students is less useful; students experience stress; as well as improving students' language literacy skills. This can be an evaluation so that online learning can be sought to be well received by students without reducing the essence of education itself.